OLAMNING LISONIY MANZARASI VA UNING USTIDAGI TADQIQOT YO‘NALISHLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the linguistic picture of the world and the direction of research conducted by linguists.
Keywords: linguistics, language, mentality, world, language, category, landscape of the universe, linguistics, concept sphere, imagination, knowledge.